Time to act: Institutional mental health support for Ukrainian academic staff during wartime - Natalia Tsybuliak; Volodymyr Vakhitov; Hanna Mytsyk; Hanna Lopatina; Maryna Nesterenko; Artem Polulyakhov; Yuriy Petrushenko (Problems and Perspectives in Management)
The study examines the impact of institutional mental health support on the career stability of academic staff at Ukrainian universities during the full-scale war, focusing on accessibility, cultural alignment, and tailored mental health initiatives provided by universities. The relevance of this topic arises from the unprecedented stressors affecting academic members in higher education institutions, who face both personal and professional challenges. A cross-sectional analytical design was employed, using an online survey distributed among 429 academic staff members. The findings reveal that nearly half of the respondents frequently contemplate changing careers, highlighting substantial job instability. Accessible mental health support is associated with a 6% decrease in career change intentions, while a supportive institutional culture further reduces these intentions by 8-9%. Notably, self-help practices emerged as the most effective support mechanism, associated with a 12% reduction in career change intentions. These findings suggest that institutions can improve retention by prioritizing and promoting accessible self-help initiatives. The study underscores the importance of structured mental health support in fostering resilience within the academic community, with implications for policy and practice in war-affected educational environments. AcknowledgmentThe research teams acknowledge the Armed Forces of Ukraine for providing safety during their research and credit their perseverance and courage for making this possible. Natalia Tsybuliak is grateful to the Ukraine Research Network@ZOiS, funded by the German Federal Ministry of Education and Research, for support in implementing the research.This work was supported by the Ministry of Education and Science of Ukraine as part of the state-funded research project 0123U105351, “Ukrainian universities in new realities: the impact of war and mechanisms for preserving the scientific and human resource potential for training specialists in high-tech fields.”